The Development of the Concept of Ma'rifat in Islamic Thought: From Classical to Contemporary - Agisna Fadilawati; Zainap Hartati; Nasir (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to explore the development of the concept of ma'rifat in Islamic thought, from classical to contemporary times, by looking at its historical journey, we will understand how this concept has been understood and translated by Islamic intellectuals and scholars in various historical periods. This study uses a qualitative method with a literature review methodology approach to analyze the development of the concept of ma'rifat in Islamic thought. In classical Islamic thought, ma'rifat is more than just knowledge; it refers to an inner experience gained through self-purification and a spiritual approach. In Sufism, ma'rifat is related to the achievement of high knowledge about the essence of the universe and God, which is obtained not only through intellectual study, but direct experience. Modern thought, as expressed by Muhammad Iqbal and Seyyed Hossein Nasr, offers a new interpretation by connecting ma'rifat to science and the challenges of the times. Both of them try to modernize this concept, responding to the influence of rationalism and materialism, and making ma'rifat a means of social and spiritual transformation. Thus, ma'rifat teaches that a true understanding of God and life requires a deep spiritual search. The findings of this study are that ma'rifat is no longer limited to individual experience, but also has broad implications in understanding the relationship between humans, science, and the reality of modern life. This study not only confirms classical thinking about ma'rifat, but also challenges the view that this concept is only esoteric and irrelevant in contemporary academic studies.